PELATIHAN HIGH ORDER THINKING SKILLS DAN EVALUASI BERBASIS ONLINE BAGI GURU SMA DI KOTA MALANG - Deny Setiawan; Siti Zubaidah; Susriyati Mahanal; Rahmi Masita (JPM PAMBUDI, 2022)
Applying HOTS and the need for effective and efficient evaluation facilities for teachers is urgent for Malang schools. This study aimed to determine the results of HOTS training and online-based evaluation in Malang. This community service aims to find out the results of HOTS training and online-based evaluation for teachers in Malang. The training target is 40 high school Biology Teachers in Malang. The activity consists of 3 stages, namely the preparation stage, the activity stage, and the evaluation stage. HOTS training and online-based evaluation positively impacted high school teachers in Malang. The average score of participants in Padlet development was 86.78%, 100% were able to make and apply Kahoot! in class, and 90.45% of participants had prepared questions according to the HOTS criteria and were able to identify their cognitive level.